Challenging Colonial Constructs: Gendered Agency in Benson and Dawson’s Short Travel Narratives - Morabit, Nadir El; Habbouch, Layachi El (Journal of Ecohumanism, 2025)
This study examines the issues of rescue, oppression, and agency in reclaiming Moroccan gendered identities through a comparative reading of S. Benson’s Thamar: The Jewess of Fez (1874), Alec Dawson’s Out Past the City Gates (1900), and A Moorish Hero and Juanita (1900). My aim is to investigate how these colonial tropes intertwine to frame women, during colonial Morocco, within the structure of oppression while offering insights into resistance and agency. This article also highlights the thematic resonance and divergence of the short stories under scrutiny, exposing how the interplay of gender, power, and identity is constructed, contested, and re-imagined. These out-of-print travel narratives elucidate the multilayered socio-historical realities of colonial Morocco, revealing the ways in which local patriarchal practices intersect with colonial ideologies to marginalize women. Benson and Dawson’s portrayals of female characters mirror Orientalist tendencies, though they also offer moments of resistance and agency, in which women reclaim their voices. By exerting their agency and recasting themselves from the pressurized roles of victim and savior, these female characters challenge and subvert oversimplified readings of domination through acts of resistance. Through its combination of feminist and postcolonial theories, this paper places these narratives within the discourse of identity, power dynamics, and representation. Furthermore, this article adds to the body of literature that foregrounds the complex roles of women as active agents and shows how these out-of-print short narratives remain vital to reshaping historical and literary understandings of gendered identities.